IMPLEMENTASI ZAKAT DALAM PRAKTEK PERBANKAN DI INDONESIA SEBAGAI PENERAPAN MAQASID SYARI’AH - Elvi Nasriandani; Hesi Eka Puteri (BORJUIS: JURNAL OF ECONOMY, 2023)
The aim of this research is to determine the impact of zakat as an application of Maqasid Syari'ah in sharia banking. The case study in this research is Bank Syari'ah Indonesia where the discussion of this research is seen from sharia banking practices in distributing zakat. The methodology in this research uses a qualitative descriptive method by collecting data using library research, namely taking scientific references from Central Statistics Agency data, books, national and international journals, the Al- Qur'an and Hadith. This research is descriptive analysis, namely complementing data or literature obtained periodically. The results of this research are that zakat can influence poverty alleviation, with the following description: 1) Ways to alleviate poverty can be by activating non-productive assets, building social networks, managing productive zakat funds to create jobs to survive, 2) Poverty can be eradicated with people who have assets, rich people carry out redistribution (encouraging rich people to have empathy for the poor or civil society. This depends on religiousness, namely the level of religiousness, rationally who wants their wealth to be locked up, they don't want a deficit, they want a surplus, things This can be explained by religion. This means that it must be supported by a level of religiousness, not only from the government budget, 3) Sharia banking accepts and manages zakat, infaq and alms, grants and waqf funds. The concept of maqasid sharia, which is to promote the benefit of the sharia itself, Imam Syatibi formulated the concept of maqasid into three, namely: Dharuriyat, Hajiyat and Tahsiniyat. while the concept of maqasid sharia offered by Abu Sahra is divided into three aspects, namely Tahzibul Fardi (Educating Individuals), Iqamah al Adl (Upholding Justice), and Maslahah (Public Interest). The implementation of the maqasid sharia concept at Bank Syari'ah Indonesia has been implemented well.